Workflow execution mechanism in grid workflow generation - ZHANG Shao-hua; XIANG Yong; SHEN Yu-zhu; SHI Mei-lin (Tongxin xuebao)
Current workflow generation researches often focus on automatic process construction and rarely discuss re-lated execution mechanism.Hence,they often lack of the support for workflow dynamic generation,activity just-in-time resource binding and manual activities.Based on pattern-oriented workflow generation planning,a synthesis execution mechanism in workflow generation was proposed It provides an abstract activity planning approach to support workflow runtime refinement and uses participant servicization approach to facilitate activity-resource just-in-time binding.It minimizes possible runtime exceptions and provides a unified support for manual and automated activities.